THE ADAPTATION PROCESS OF CHRISTIANITY, JUDAISM, AND ISLAM TO CHINESE SOCIAL LIFE (17th – 18th CENTURIES) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
China, with its rich history and spiritual heritage, is recognized as one of the cradles of world civilization. Over the centuries, various religious beliefs have developed and flourished in this land, leading to the establishment of profound spiritual values. Among these, Christianity, Judaism, and Islam also spread throughout China and left their mark on the cultural life of the people living there. This article explores the history of the spread of Christianity, Judaism, and Islam in China, their influence on the country’s political, economic, and spiritual life, as well as the condition of these religions during the 17th–18th centuries. Among the three major world religions, Christianity entered China after Buddhism but before Islam, making it the second to arrive. It is believed that the first wave of Christianity reached China in the early centuries of the Common Era. The Jewish population in China has been living in the region for over 2,000 years. They arrived through various routes, and the number of communities has changed over time. Nevertheless, their contribution to the development of China is significant. The first arrival of Muslims in China dates back to the 7th century CE. Later, by the 17th century, Islam experienced a stage of growth in the region. During this period, Islamic sources were translated into Chinese, madrasas began teaching from core Islamic texts, and the Han Kitabs — Chinese commentaries on Islamic sources — were developed.